The Influence of Instructional Leadership and Data-Based Planning on School Quality: A Study of Public Elementary Schools in Gunem District Rembang Regency - Fibrianti, Ummil Makarim; Egar, Ngasbun; Abdullah, Ghufron (Journal of Educational Sciences, 2025)
Improving the quality of basic education is an essential foundation for developing competitive human resources. However, many schools face persistent challenges, particularly related to leadership effectiveness and the limited use of data in planning. This study aims to examine the influence of instructional leadership and data-based planning on the quality of public elementary schools in Gunem District, Rembang Regency. The research employed a quantitative explanatory approach with a sample of 108 respondents, consisting of principals and teachers selected through proportional random sampling. Data were collected using a validated Likert-scale questionnaire and analyzed using multiple linear regression. The results show that both instructional leadership and data-based planning have a positive and significant effect on school quality, both individually and simultaneously. The simultaneous test revealed that the two variables together explained 35.6% of the variance in school quality, demonstrating their complementary impact. In conclusion, strong instructional leadership combined with systematic data-driven planning substantially improves school quality, while other external factors also play a role in achieving sustainable educational improvement.